2016
DOI: 10.1007/s10120-016-0663-8
|View full text |Cite
|
Sign up to set email alerts
|

Results of a nation-wide retrospective study of lymphadenectomy for esophagogastric junction carcinoma

Abstract: Complete nodal clearance along the distal portion of the stomach offers marginal survival benefits for patients with EGJ cancers less than 4 cm in diameter. The optimal extent of esophageal resection and the benefits of mediastinal node dissection remain issues to be addressed in managing patients with esophagus-predominant EGJ cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
152
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(164 citation statements)
references
References 28 publications
(26 reference statements)
5
152
1
6
Order By: Relevance
“…1b). Although the report from Yamashita et al [5] and our data showed growing trends of EGJ adenocarcinoma, these were attributed to an increase of the elderly population in Japan. The search in PubMed revealed that there were no reports examining the incidence trend of EGJ adenocarcinoma in other Asian countries, such as Korea or China.…”
Section: Recent Trends Of Egj Adenocarcinoma In Japancontrasting
confidence: 44%
See 1 more Smart Citation
“…1b). Although the report from Yamashita et al [5] and our data showed growing trends of EGJ adenocarcinoma, these were attributed to an increase of the elderly population in Japan. The search in PubMed revealed that there were no reports examining the incidence trend of EGJ adenocarcinoma in other Asian countries, such as Korea or China.…”
Section: Recent Trends Of Egj Adenocarcinoma In Japancontrasting
confidence: 44%
“…They demonstrated that the proportion of Siewert type II increased between 1962 and 2005, but that of Siewert type I remained around 1% over 44 years. Recently, Yamashita et al [5] showed that the number of surgically resected cases of EGJ adenocarcinoma were gradually increased between 2001 and 2010, using a questionnaire-based national retrospective study in Japan. In their article, EGJ adenocarcinoma was defined as tumors with epicenter located within 2 cm proximal or distal to the anatomical EGJ by the Japanese classification of gastric cancer (14th edition, Japanese only).…”
Section: Recent Trends Of Egj Adenocarcinoma In Japanmentioning
confidence: 99%
“…Dissection of mediastinal lymph nodes could be indicated and may, in some cases, even be recommended for patients with junctional cancer, given the presence of long‐term survivors among patients with metastases to such lymph nodes 15. Furthermore, patients with para‐aortic lymph node metastases beyond the a2 and b1 regions could still be indicated for surgery pending marked shrinkage of these nodes during chemotherapy which, originally, would have been cause for palliation.…”
Section: Lymph Node Metastasismentioning
confidence: 99%
“…Yamashita et al reported clinical records of 2807 EGJ carcinoma patients without preoperative therapy in Japan [20]. There are obvious unbalances in terms of lymph node dissection rate according to histology and the main tumor location.…”
Section: Lymph Node Metastasis Of Eacmentioning
confidence: 99%